Perencanaan Kebutuhan Bahan Baku Produk Kusen dengan Metode MRP - Anidia, Tisna; Hermawan, Asep; Haerudin, Yayan Heru (Metode : Jurnal Teknik Industri, 2025)
Uncontrolled raw material inventory can lead to either excess or shortage of stock, thereby hampering the production process. This condition is also experienced by CV. Arafah Jaya, a manufacturer of window and door frames, where frequent stockpiling of raw materials results in high inventory costs. This study aims to systematically plan raw material requirements using the Material Requirement Planning (MRP) method. Demand forecasting was carried out using the Moving Average and Exponential Smoothing methods, with the evaluation showing that Exponential Smoothing produced more accurate results. The forecasting data were then used to develop the Master Production Schedule (MPS) as the basis for calculations in the MRP system. The analysis continued with the application of three lot-sizing techniques, namely Lot for Lot (LFL), Economic Order Quantity (EOQ), and Period Order Quantity (POQ). The comparison results indicate that the LFL technique yields the lowest total procurement cost of raw materials, amounting to IDR 7,290,380. Thus, the LFL technique is considered the most efficient method for controlling raw material procurement at CV. Arafah Jaya.